The Short and Long Run Effect of Domestic Investment, Foreign Direct Investment and Renewable Energy on Economic Development: Evidence from Cameroon - Afumbom, Nges Shamaine; Fosah, Mah-Soh Glenice; Dinga, Gildas Dohba (Asian Development Policy Review, 2020)
The purpose of this paper is to examine the short and long-run effect of domestic investment, foreign direct investment and renewable energy on economic development in Cameroon. To achieve this, the study makes use of the Autoregressive Distributed Lag Model and Bound test for co‐integration to establish the short and long‐run relationships. The results show that in the short‐run domestic investment and renewable energy both have a positive and significant effect on economic development while foreign direct investment has a negative but significant effect on economic growth. The long‐run equilibrium shows a significant and positive relationship between domestic investment and foreign direct investment on economic development while population growth rate and renewable energy show a negative relationship with economic growth. Official development aid inflow is found to positively affect economic development. However, this finding is seen to be statistically insignificant. The study therefore recommends that the state should continually encourage domestic savings, grant investment incentives as well as improved infrastructural facilities to spur the investment level and consequently economic development. Furthermore, the government should improve the business environment, set up a facilitating structure for both foreign and domestic investors and free movement of capital flows to attract FDI, which raises economic growth hence development.